The influence of the dynamics features of the trapped particles on a spectrum of their oscillations - Buts, V.A.; Vavriv, D.M.; Tarasov, D.V. (Вопросы атомной науки и техники, 2013)
Some features of dynamics of ensembles of coupled linear and nonlinear oscillators are investigated. It is shown that spectral characteristics of this dynamics essentially depend not only on quantity of the oscillators making the ensemble, but also on features of motion of each oscillator. In particular, at chaotic motion – on the moments of their chaotic dynamics. Special attention is turned on appearance of LF dynamics of ensemble. In this case there is a possibility of an effective exchange of energy between HF and LF oscillations.